Comparing traditional Teaching Methods with PBL in Science and their Impact on Students’ Achievement at Elementary Level - Dr. Muhammad Aqeel Raza; Fayyaz Ahmad; Najam Abbas (Indus Journal of Social Sciences, 2025)
The designed study was used to compare traditional teaching methods with PBL in science and their impact on achievement of eighth graders. The objectives of the study were to assess achievement of the student’s, to practice problem based learning through activities, and to evaluate student’s achievement after problem based activities. The study population was encompassed all students of 8th grade (21150) within District Muzaffar Garh. Sample size was 60 students from the same district. Thirty students out of 35 were selected from Government Boys Elementary School Waan Pitafi by using simple random technique as experimental group. Thirty students out of 40 were selected from Government Boys Elementary School Ishaq Wala by using simple random technique as control group. The research design was pretest-posttest and Quasi experimental in nature. Problem based learning treatment was applied. The experimental group was treated with problem based learning and the control group was taught through traditional lecture-based methods. Data was collected from the control and experiment groups before and after 9 month problem-based learning through pre-test and posttest. After collection of data, analysis of the data was done through descriptive statistics by finding out means. The findings of the study revealed that achievement scores of experimental group were better as compared to scores of control group. The difference in means of experimental and control group in pretest is very small than difference in means of experimental group and control groups in post-test. It depicts through problem based learning students’ achievement scores are improved.